Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 13201 by Tinkutara last updated on 16/May/17

In a ΔABC prove that:  ((sin A + sin B)/2) ≤ sin (((A + B)/2))

InaΔABCprovethat:sinA+sinB2sin(A+B2)

Commented by ajfour last updated on 16/May/17

kindly check if  B=0 and A=−(π/3) .

kindlycheckifB=0andA=π3.

Answered by ajfour last updated on 16/May/17

A+B=π−C  ((A+B)/2) = (π/2)−(C/2)  ⇒ sin (((A+B)/2))=cos (C/2) > 0    sin A+sin B=2sin (((A+B)/2))cos (((A−B)/2))  ((sin A+sin B)/(2sin (((A+B)/2)))) = cos (((A−B)/2))≤1  hence  ((sin A+sin B)/2) ≤ sin (((A+B)/2))  sin (((A+B)/2))>0   so inequality                                 doesn′t change .

A+B=πCA+B2=π2C2sin(A+B2)=cosC2>0sinA+sinB=2sin(A+B2)cos(AB2)sinA+sinB2sin(A+B2)=cos(AB2)1hencesinA+sinB2sin(A+B2)sin(A+B2)>0soinequalitydoesntchange.

Answered by b.e.h.i.8.3.4.1.7@gmail.com last updated on 16/May/17

sin(((A+B)/2))=sin(90−(C/2))=cos(C/2)  sinA+sinB=2sin((A+B)/2)cos((A−B)/2)=  =2sin(90−(C/2))cos(((A−B)/2))=2cos(C/2)cos((A−B)/2)  ⇒((2cos(C/2)cos((A−B)/2))/2)≤cos(C/2)⇒  ⇒cos((A−B)/2)≤1 (alwyes true)  ∀x∈R:cosx≤1

sin(A+B2)=sin(90C2)=cosC2sinA+sinB=2sinA+B2cosAB2==2sin(90C2)cos(AB2)=2cosC2cosAB22cosC2cosAB22cosC2cosAB21(alwyestrue)xR:cosx1

Answered by b.e.h.i.8.3.4.1.7@gmail.com last updated on 16/May/17

sinA+sinB=(a/(2R))+(b/(2R))=((a+b)/(2R))  sin(((A+B)/2))=cos(C/2)=(√((1+cosC)/2))=  =(√((1+((a^2 +b^2 −c^2 )/(2ab)))/2))=(√(((a+b+c)(a+b−c))/(4ab)))  =(√((p(p−c))/(ab)))     (p=((a+b+c)/2),S=((abc)/(4R)))  ⇒((a+b)/(4R))≤(√((p(p−c))/(ab)))⇒(((a+b)^2 )/(16R^2 ))≤((p(p−c))/(ab))⇒  (((a+b)^2 )/((a^2 b^2 c^2 )/S^2 ))≤((p(p−c))/(ab))⇒S^2 .(((a+b)^2 )/(abc^2 ))≤p(p−c)⇒  p(p−a)(p−b)(p−c)(((a+b)^2 )/(abc^2 ))≤p(p−c)⇒  (p−a)(p−b)(a+b)^2 ≤abc^2 ⇒  (c+b−a)(c−b+a)(a+b)^2 ≤4abc^2 ⇒  (c^2 −(b−a)^2 )(a+b)^2 ≤4abc^2 ⇒  c^2 ((a+b)^2 −4ab)≤(b−a)^2 (b+a)^2 ⇒  c^2 (b−a)^2 ≤(b−a)^2 (b+a)^2 ⇒c^2 ≤(b+a)^2 ⇒  c≤b+a   .■  (proved)  note:if a=b⇒((sinA+sinB)/2)=sinA≤sin(((A+A)/2))=sinA.

sinA+sinB=a2R+b2R=a+b2Rsin(A+B2)=cosC2=1+cosC2==1+a2+b2c22ab2=(a+b+c)(a+bc)4ab=p(pc)ab(p=a+b+c2,S=abc4R)a+b4Rp(pc)ab(a+b)216R2p(pc)ab(a+b)2a2b2c2S2p(pc)abS2.(a+b)2abc2p(pc)p(pa)(pb)(pc)(a+b)2abc2p(pc)(pa)(pb)(a+b)2abc2(c+ba)(cb+a)(a+b)24abc2(c2(ba)2)(a+b)24abc2c2((a+b)24ab)(ba)2(b+a)2c2(ba)2(ba)2(b+a)2c2(b+a)2cb+a.(proved)note:ifa=bsinA+sinB2=sinAsin(A+A2)=sinA.

Answered by b.e.h.i.8.3.4.1.7@gmail.com last updated on 16/May/17

we can prove that:  ((sinA+sinB+sinC)/3)≤sin(((A+B+C)/3))=((√3)/2)  sinA+sinB+sinC≤((3(√3))/2)

wecanprovethat:sinA+sinB+sinC3sin(A+B+C3)=32sinA+sinB+sinC332

Answered by b.e.h.i.8.3.4.1.7@gmail.com last updated on 16/May/17

(((sinA+sinB)/2))^2 ≤sin^2 (((A+B)/2))=sin^2 (90−(C/2))=cos^2 (C/2)  sin^2 A+2sinAsinB+sin^2 B≤2(1+cosC)=2(1+cos(180−A−B))  1−cos^2 A+2sinAsinB+1−cos^2 B≤2−2cosA.cosB+2sinA.sinB  −cos^2 A+2cosA.cosB−cos^2 B≤0  cos^2 A−2cosA.cosB+cos^2 B≥0  (cosA−cosB)^2 ≥0   .■(proved)

(sinA+sinB2)2sin2(A+B2)=sin2(90C2)=cos2C2sin2A+2sinAsinB+sin2B2(1+cosC)=2(1+cos(180AB))1cos2A+2sinAsinB+1cos2B22cosA.cosB+2sinA.sinBcos2A+2cosA.cosBcos2B0cos2A2cosA.cosB+cos2B0(cosAcosB)20.(proved)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com